1979
DOI: 10.1111/j.1440-1681.1979.tb01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profile of a New Coronary Vasodilator Drug, 2-Nicotinamidoethyl Nitrate (Sg-75)

Abstract: 1. In anaesthetized, open-chest dogs, 2-nicotinamidoethyl nitrate (SG-75) administered intravenously (0.3-1 mg/kg) or intraduodenally (3 mg/kg) produced decrease in systemic blood pressure, coronary resistance, heart rate and an increase in coronary sinus outflow, but virtually no change in myocardial oxygen consumption and atrioventricular conduction. The effects of SG-75 administered intraduodenally emerged within a few minutes after dosing and lasted over about 1 h. 2. In isolated, blood-perfused sino-atria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 11 publications
4
56
1
Order By: Relevance
“…This beneficial action of nicorandil on the ischaemic myocardium is shared by nitroglycerine and propranolol but not by dipyridamole (Ichihara et al, 1979;Abiko & Sakai, 1980;Shibano & Abiko, 1983). The beneficial action of nicorandil is probably because of the coronary vasodilator effect of the drug (Uchida et al, 1978;Taira, et al, 1979;Sakai et al 1981), permitting an increase in perfusion of the ischaemic area by increased blood supply from the non-ischaemic area, in which blood flow has been increased. This assumption is based on the findings of Ogawa et al, 1982.…”
Section: Discussionmentioning
confidence: 99%
“…This beneficial action of nicorandil on the ischaemic myocardium is shared by nitroglycerine and propranolol but not by dipyridamole (Ichihara et al, 1979;Abiko & Sakai, 1980;Shibano & Abiko, 1983). The beneficial action of nicorandil is probably because of the coronary vasodilator effect of the drug (Uchida et al, 1978;Taira, et al, 1979;Sakai et al 1981), permitting an increase in perfusion of the ischaemic area by increased blood supply from the non-ischaemic area, in which blood flow has been increased. This assumption is based on the findings of Ogawa et al, 1982.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the finding of Maruyama et al (7) that nicorandil has a potent broncho-dilating activity. It has been reported that nicorandil has a nitrate moiety in its chemical structure which plays an important role in the pharmacological activity of this drug (2,5). Recently, Maru yama et al (7) also confirmed that in the arterially blood-perfused preparation of the dog trachea in situ, the nitrate site of nicorandil plays an important role in in creasing its activity to produce both tracheal dilatation and tracheal vasodilation.…”
Section: Discussionmentioning
confidence: 51%
“…Thus, it seems that NCR has a relatively selective action on the vasculature. This compound has a nitrate moiety in its chemical structure, and this site undoubtedly plays an important role in the development of its pharmacological activity (2,5). Recently, the effects of locally applied nitroglycerin (NTG) (6) and NCR (7) on the tracheal musculature and vasculature were investi gated in the arterially blood-perfused pre paration of the dog trachea (8).…”
mentioning
confidence: 99%
“…Recently, it has also been shown that in rats the vasodepressor effect of cromakalim on systemic arterial pressure was specifically antagonized by glibenclamide, an oral antidiabetic drug (Cavero et al, 1988). Nicorandil exerts a vasodepressor effect (Uchida et al, 1978;Taira et al, 1979;Sakai et al, 1981) (Fleckenstein, 1981) and nearly equipotent to nicorandil as a vasodilator (Sakai et al, 1981).…”
Section: Introduction Methodsmentioning
confidence: 99%